Origins of the threshold for surgical intervention in intra-articular distal radius fractures. (1st September 2021) - Esworthy, George Philip; Johnson, Nick A.; Divall, Pip; Dias, Joseph J.
Abstract : Aims: The aim of this study was to identify the origin and development of the threshold for surgical intervention, highlight the consequences of residual displacement, and justify the importance of accurate measurement. Methods: A systematic review of three databases was performed to establish the origin and adaptations of the threshold, with papers screened and relevant citations reviewed. This search identified papers investigating functional outcome, including presence of arthritis, following injury. Orthopaedic textbooks were reviewed to ensure no earlier mention of the threshold was present. Results: Knirk and Jupiter (1986) were the first to quantify a threshold, with all their patients developing arthritis with > 2 mm displacement. Some papers have discussed using 1 mm, although 2 mm is most widely reported. Current guidance from the British Society for Surgery of the Hand and a Delphi panel support 2 mm as an appropriate value. Although this paper is still widely cited, the authors published a re-examination of the data showing methodological flaws which is not as widely reported. They claim their conclusions are still relevant today; however, radiological arthritis does not correlate with the clinical presentation. Function following injury has been shown to be equivalent to an uninjured population, with arthritis progressing slowly or not at all. Joint space narrowing has also been shown to often be benign. Conclusion: Knirk and Jupiter originated the threshold value of 2 mm. The lack of correlation between the radiological and clinical presentations warrants further modern investigation. Measurement often varies between observers, calling a threshold concept into question and showing the need for further development in this area. The principle of treatment remains restoration of normal anatomical position. Cite this article: Bone Joint J 2021;103-B(9):1457–1461.